Review of The Evaluation Exchange, Volume XI(1), XI(2), and XI(3) - Brandon W. Youker (The Evaluation Center at Western Michigan University, 2006)
The Evaluation Exchange is a free, online evaluation periodical (http://www.gse.harvard.edu/hfrp/eval.html) published by the Harvard Family Research Project (HFRP) three or four times annually. It is aimed at addressing issues that program evaluators frequently encounter. The journal emphasizes innovative methods and approaches to evaluation, emerging trends in practice, and practical applications of evaluation theory. It is designed to serve as a medium for evaluators, program practitioners, funders, and policymakers. The journal is divided into five sections; (i) Theory & Practice; (ii) Promising Practices; (iii) Spotlight; (iv) Evaluations to Watch, and (v) Beyond Basic Training. The submissions are typically very brief (2-4 pages) and succinct. Each issue has an overarching theme or topic. The three most recent issues included Complementary Learning (spring 2005), Evaluation Methodology (summer 2005), and Democratic Evaluation (fall 2005).